2021
DOI: 10.1017/s0144686x21001392
|View full text |Cite
|
Sign up to set email alerts
|

Care precarity among older British migrants in Spain

Abstract: Northern European international retirement migrants are often viewed as affluent and use migration as a route to a better quality of life. However, as these migrants transition into the ‘fourth age’, the onset of age-related illnesses, frailty and care needs can lead to increased levels of risk and insecurity. Through 34 qualitative interviews with older British migrants in Spain, the paper explores how these migrants access and experience care as they age. It draws on a lens of precarity that allows an unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Interviews with 200 retirement migrants in Spain (Calzada 2018) showed that most migrants used formal state care as a last resort and attempted to get help from personal networks and private care providers first. The lack of communication resulted from migrants not speaking the language, which became problematic when they needed health care services that were provided in only the local language (Hall 2021;Hall and Hardill 2016;Hardill et al 2005;Kohno et al 2016). Some retirement migrants encountered other barriers, such as a lack of integration with their legal status, failure to meet criteria for public help, or lacking the financial means for access to health care (Hall 2021).…”
Section: Health and Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviews with 200 retirement migrants in Spain (Calzada 2018) showed that most migrants used formal state care as a last resort and attempted to get help from personal networks and private care providers first. The lack of communication resulted from migrants not speaking the language, which became problematic when they needed health care services that were provided in only the local language (Hall 2021;Hall and Hardill 2016;Hardill et al 2005;Kohno et al 2016). Some retirement migrants encountered other barriers, such as a lack of integration with their legal status, failure to meet criteria for public help, or lacking the financial means for access to health care (Hall 2021).…”
Section: Health and Well-beingmentioning
confidence: 99%
“…The lack of communication resulted from migrants not speaking the language, which became problematic when they needed health care services that were provided in only the local language (Hall 2021;Hall and Hardill 2016;Hardill et al 2005;Kohno et al 2016). Some retirement migrants encountered other barriers, such as a lack of integration with their legal status, failure to meet criteria for public help, or lacking the financial means for access to health care (Hall 2021). Therefore people sometimes fell back on other forms of support.…”
Section: Health and Well-beingmentioning
confidence: 99%
“…On the other hand, we asked about return prevision, that is, if the respondents think that in some future scenarios it is probable for them to return to the United Kingdom, as it can be seen in Table 8. Most of the respondents do not want to return (87.4%), which is a higher number than previous surveys suggest, indicating that return intentions were lower in 2020 than in 2016 (in Hall, 2023, return intentions were 71.3%). This suggests that more older British population living in Spain intend to stay than before Brexit ( t = −5685.610; df = 642; p = 0.000).…”
Section: Resultsmentioning
confidence: 55%
“…As it is well known, most British migrants migrate to Spain for lifestyle reasons rather for work (O'Reilly, 2000). Therefore, Spain is the most common destination for older, retired British migrants, and there are approximately 117,000 British nationals receiving a British state pension in Spain (Hall, 2023). This figure does not however include those who are retired and under state pension age or those who are not legally resident in Spain, and therefore estimates have suggested that there are up to a million older British nationals living in Spain for or all or most of the year (Benton, 2017).…”
Section: Return Migration and The British In Spainmentioning
confidence: 99%
“…Numerous studies have been undertaken on lifestyle migration, for example, in Southern Europe, British retirees in Spain (Hall, 2023), Northern European retired residents in eight regions of southern Europe and the Canary Islands (Casado-Díaz et al ., 2004), and many in other regions, including Southeast Asia (Horn et al. , 2015; Howard, 2008; Husa et al.…”
Section: Introductionmentioning
confidence: 99%